The impact of athletes` self-identity on employment readiness: the mediating role of professional identity - Zhao, M.; Liu, J.; Lyu, D. (Frontiers in Psychology, 2025)
Introduction: Athletes` self-identity and professional identity are crucial factors influencing their career development. Against the backdrop of China`s competitive sports system transformation, the employment preparation status of athletes requires urgent attention. This study aims to investigate the internal mechanisms among athletes` self-identity, professional identity, and employment preparation adequacy.